2020
DOI: 10.1021/jacs.0c02673
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Cross-Electrophile Coupling of Aryl Chlorides with Primary Alkyl Chlorides

Abstract: Alkyl chlorides and aryl chlorides are among the most abundant and stable carbon electrophiles. Although their coupling with carbon nucleophiles is well developed, the cross-electrophile coupling of aryl chlorides with alkyl chlorides has remained a challenge. We report here the first general approach to this transformation. The key to productive, selective crosscoupling is the use of a small amount of iodide or bromide along with a recently reported ligand, pyridine-2,6-bis(Ncyanocarboxamidine) (PyBCam CN ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 73 publications
2
98
0
Order By: Relevance
“…Notably, screening the loading of Zn in the 0.1–1.0 equivalent range confirmed that only 0.25 equivalents were required (entries 8–11). By contrast, previous literature using the Ni/Zn combination involves super‐stoichiometric zinc [15] . When air remained within the reaction vessel (entry 13) reaction efficiency was reduced, as thiols, not surprisingly, were oxidized under these mildly basic conditions (pH 7–9) to disulfides [16] …”
Section: Resultsmentioning
confidence: 81%
“…Notably, screening the loading of Zn in the 0.1–1.0 equivalent range confirmed that only 0.25 equivalents were required (entries 8–11). By contrast, previous literature using the Ni/Zn combination involves super‐stoichiometric zinc [15] . When air remained within the reaction vessel (entry 13) reaction efficiency was reduced, as thiols, not surprisingly, were oxidized under these mildly basic conditions (pH 7–9) to disulfides [16] …”
Section: Resultsmentioning
confidence: 81%
“…9). One undergoes the oxidative addition of ary halides to the transition metals [47][48][49][50][51][52][53][54] . The other starts with the formation of the aryl radical anion (ArX• -) by the single electron transfer (SeT) from catalysts to ary halides 45,46,56 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is desired to overcome this problem because a new use of water as the green reducing agent to enable the reductive transformations of organic substances can be developed by this way. In addition, the reductive coupling of aryl or alkyl halides is of great significance in modern organic synthesis [47][48][49][50][51][52][53][54][55][56] , which has prompted us to select this kind of reaction as the model reaction to make our idea come true. Encouraged by prior success in applying carbon nitride-supported transition metal (M/g-C 3 N 4 ) into photocatalytic water splitting, [57][58][59][60][61][62][63][64][65] we selected this kind of semiconductor to achieve our goals.…”
Section: Fig 1 Coupling Organic Reactions With Photocatalytic Half-reaction Of Water Splittingmentioning
confidence: 99%
“…29,30 Developing cheap salts for green and safe hydrogen storage and for replacing environmentally unfriendly metals as reductants in reductive cross-couplings is a long-standing goal. [31][32][33][34][35][36][37][38] In addition, the smaller distinction between two different alkyl coupling partners is a tough challenge compared with the distinction between aryl and alkyl halide coupling partners. 39 Traditionally, the direct reductive cross-couplings of electrophilic partners are realized via preactivation of alkyl halides by a metal reductant to avoid precast organometallic reagents (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%